The Relative Returns to Workforce Investment Act–Supported Training in Florida by Field, Gender, and Education and Ways to Improve Trainees’ Choices - Jacobson, Louis; Davis, Jonathan (Journal of Labor Economics, 2017)
The key finding of this paper is that women Workforce Investment Act (WIA) trainees select higher-return fields than men but men usually have higher returns than women in the same field. Among men, the higher the level of education, the greater the proportion who select high-return fields; the reverse is true for women. Finally, most men select fields that are predominantly male, and vice versa for women, even though gains among men and women making unconventional choices are often large. Thus, there is considerable room for men and women to increase their gains by altering their choice of field.